KOMUNIKASI BIMBINGAN ORANG TUA PADA ANAK DALAM UPAYA MENINGKATKAN PRESTASI BELAJAR MATEMATIKA - Denti Novia Sari; Lamhir Syam Sinaga; Evi Lorita (UNIVED PRESS, Universitas Dehasen Bengkulu, 2016)
This study aimed to determine the children’s parent communication in improving learning achievement in Mathematics. This was a qualitative descriptive research. Datas were collected by interviews, observation and documentation techniques. There were two groups of informants in this research, the key informant which consisted of a Math teacherin class VI Elementary School Number 27 Bengkulu and principal informant which consisted of two children’s parent, Mrs. Desi Yanti and Lini Marlina. Communication messages done by parents in improving achievement in Mathematics subject were: (1) providing guidance and advice, (2) supervision of learning, (3) giving rewards and punishments, (4) the fulfillment of learning (5) creating condusive atmosphere in studying, (6) paying attention to children’s health, and (7) providing handy hints. Based on the results of research and discussion, it was concluded that the instructional communication role of parents in improving learning achievement of Mathematics has been running quite well in pre-instructional stage and directing stage, also in follow-up evaluation stage. But in the aspect of instructional or learning it’s not fully completed. Keywords: communication between parents and children, achievement in Mathematics subject, instructional communication